Clinical learning environment and graduating nursing students' competence: a multi-country cross-sectional study - Visiers-Jiménez, Laura (2022)
The purpose of this study was to explore nursing students' perceptions of their final clinical learning environment and its association with their self-assessed competence, satisfaction with nursing education, and turnover intentions at graduation in six European countries. A multi-country comparative cross-sectional study was conducted with nursing students (n = 1746) from the Czech Republic, Finland, Italy, Portugal, Slovakia, and Spain using the Nurse Competence Scale and the Clinical Learning Environment and Supervision scale. Nursing students' overall perceptions of their final clinical learning environment and supervision were positive in all the countries studied. The correlation between the students' perceptions of their final clinical learning environment and competence was statistically significant and positive. Satisfaction with the nursing program and clinical practicum and no consideration of career change were related to positive perceptions of the final clinical learning environment. Highlighting the importance of the supervisory relationship and pedagogical atmosphere, nursing students' positive perceptions of the final clinical learning environment and supervision contribute to a better level of self-assessed competence and satisfaction with the nursing program and clinical practicum, leading to lower turnover intentions.